Alarm Activations Analysis for Performance Enhancement in a Semiconductor Facility. Issue 6 (2022) - Al-kharaz, Mohammed; Ananou, Bouchra; Ouladsine, Mustapha; Combal, Michel; Pinaton, Jacques
Abstract: The performance improvement of alarm systems helps enhance control, operator effectiveness, facility up-times, safety, and eventually reduce losses. During the facility's operation, a large amount of alarm system data are collected and historized. Valuable information can be extracted from the alarms history and used to enrich the facility's control and performance, which prompted the development of alarm management methods and resulted in a need to transform such information into useful visual forms. These visual forms need to help facility operators and engineers understand alarm system behavior and facilitate decision making. This paper presents a framework to monitor and evaluate the alarm system's performance in a semiconductor manufacturing facility. We provide a mathematical formulation of elaborated calculations in this context. We also demonstrate the proposed framework's effectiveness using a real dataset issued from the ST-Rousset semiconductor manufacturing facility.